2020
DOI: 10.1177/1071181320641337
|View full text |Cite
|
Sign up to set email alerts
|

Visual Blood Loss Estimation Accuracy: Directions for Future Research Based on a Systematic Literature Review

Abstract: Visual blood loss estimation occurs in a variety of medical contexts and may impact everything from interventions by immediate responders to the likelihood of receiving blood transfusions in a hospital setting. However, research suggests that visual blood loss estimation is inaccurate for laypeople and medical professionals. The aim of the current study was to conduct a systematic literature review to determine the current state of knowledge on visual blood loss estimation accuracy and identify directions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Additionally, in line with the findings of Phillips et al (2020a), we found that blood loss was underestimated more for the female victim than the male victim. This effect has not otherwise been examined in the literature in this context (Phillips et al, 2020b) but is consistent with findings that males are more likely to receive assistance in trauma situations (Faul et al, 2016) and receive higher quality pre-hospital care (Koval et al, 2006;Wahlin et al, 2016). Unlike Phillips et al (2020a), the current study found an interaction between victim gender and volume.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, in line with the findings of Phillips et al (2020a), we found that blood loss was underestimated more for the female victim than the male victim. This effect has not otherwise been examined in the literature in this context (Phillips et al, 2020b) but is consistent with findings that males are more likely to receive assistance in trauma situations (Faul et al, 2016) and receive higher quality pre-hospital care (Koval et al, 2006;Wahlin et al, 2016). Unlike Phillips et al (2020a), the current study found an interaction between victim gender and volume.…”
Section: Discussionsupporting
confidence: 88%
“…However, there are relatively few studies of how medical laypeople perceive blood loss. A recent review of 72 articles examining visual blood loss estimation (Phillips et al, 2020b) revealed that over 90% of the studies involved medical professionals. As a result, many of the experimental stimuli used were clinically relevant but not necessarily representative of the situations in which medical laypeople might need to visually estimate blood loss and determine a course of action.…”
Section: Introductionmentioning
confidence: 99%
“…The current method for estimating blood loss in laparoscopic surgery entails summing the weight of the used gauzes and the fluid aspirated by the suction device. Unfortunately, this method is inconvenient and labor-intensive, requiring additional manpower, and is not conductive to establishing a real-time intraoperative blood loss monitoring system 22 . Consequently, there is a need for an objective and automated EBL estimation during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Blood loss associated with surgical procedures, trauma, or injuries can be lethal depending on the extremity of the damage [ 1 ] . Conventional hemostatic techniques, such as suturing or cotton gauzes, are inefficient in achieving rapid hemostasis.…”
Section: Introductionmentioning
confidence: 99%